Investigating the Success Rate of Vaginal Delivery After Cesarean Section and Its Associated Factors in Afghan Women: Insights from a Maternity Hospital in Kabul - Golzareh P; Baha H; Aram F; Stanikzai MH; Rabizada R; Jafari M (International Journal of Women's Health)
Parvin Golzareh,1 Halima Baha,2 Fahima Aram,3 Muhammad Haroon Stanikzai,4 Razia Rabizada,5 Massoma Jafari6 1Department of Advanced Midwifery Skills, School of Midwifery, Kabul University of Medical Sciences “Abu Ali Ibn Sina”, Kabul, Afghanistan; 2Department of Normal Midwifery, School of Midwifery, Kabul University of Medical Sciences “Abu Ali Ibn Sina”, Kabul, Afghanistan; 3Department of Gynecology, School of Midwifery, Kabul University of Medical Sciences “Abu Ali Ibn Sina”, Kabul, Afghanistan; 4Department of Public Health, Faculty of Medicine, Kandahar University, Kandahar, Afghanistan; 5Department of Oral Health, School of Stomatology, Kabul University of Medical Sciences “Abu Ali Ibn Sina”, Kabul, Afghanistan; 6Department of Health Profession Education Research, University of Toronto, Ontario, CanadaCorrespondence: Muhammad Haroon Stanikzai, Department of Public Health, Faculty of Medicine, Kandahar University, District # 10, Kandahar, 3801, Afghanistan, Tel +93704775578, Email haroonstanikzai1@gmail.comBackground: Vaginal Birth After Cesarean delivery (VBAC) is widely regarded as one of the most effective methods to reduce unnecessary Cesarean section and their complications. Despite its proven benefits, data on the success rate of VBAC and the associated factors remain scarce in Afghanistan. This study aimed to address this gap by determining the VBAC success rate and identifying its associated factors in a maternity hospital in Kabul, Afghanistan.Methods: This cross-sectional study was conducted at Malalai Obstetrics and Gynecology Hospital in Kabul, Afghanistan. The study sample included women with a history of previous cesarean section who visited the hospital between March 21 and September 22, 2023. Demographic and clinical information were collected from client files. Descriptive statistics were used to summarize the demographic and clinical characteristics of the study sample. The association between VBAC and various categorical variables were examined using chi-square tests, with a significance level set at p < 0.05. Logistic regression analysis was performed to identify independent predictors of VBAC, with VBAC as the outcome variable and multiple predictors included in the model.Results: Among the 567 women included in the study, 449 (79.2%) had a successful VBAC. Factors associated with successful VBAC and their adjusted odds ratio (95% CI) were lower gestational age: 1.25 (1.05– 1.48), absence of gestational hypertension: 2.71 (1.26– 5.85), cervical dilation of > 4 cm on admission: 2.77 (1.38– 5.55), effacement of ≥ 50% on admission: 2.13 (1.04– 4.35), and absence of fetal distress: 7.35 (4.29– 12.6).Conclusion: The rate of successful VBAC observed in this study is at a high level (79.2%). This study is the first study to determine the VBAC success rate and its associated factors in Afghanistan. Further research is needed to validate these findings and explore additional factors influencing VBAC success.Keywords: vaginal delivery after cesarean, dilatation, effacement, fetal distress, gestational age, Afghanistan